Mediation by self-efficacy in the relation between social support and dietary intake in low-income postpartum women who were overweight or obese. (1st September 2019) - Chang, Mei-Wei; Schaffir, Jonathan; Brown, Roger; Wegener, Duane T.
Abstract: Purpose: Using baseline data from a prevention of weight gain intervention study, we investigated whether self-efficacy mediated the relations between social support and dietary intake of saturated fat, fast food, fruit and vegetable in low-income postpartum women who were overweight or obese. Methods: Participants (N = 740) completed validated measures of self-reported social support, self-efficacy, and dietary intake of saturated fat, fast food, fruit and vegetable. We performed composite indicator structural equation modeling to test the mediation effect. Effect size was calculated using proportion of maximum possible (POMP) scores in the endogenous variables (e.g., fast food) per unit change in the exogenous variable. Results: When including the influence of self-efficacy as a mediator, social support indirectly influenced dietary intake of saturated fat (p ≤ 0.001, POMP = −0.77%), fast food (p ≤ 0.001, POMP = −0.28%), and fruit and vegetable (p ≤ 0.001, POMP = 0.53%). Thus, these data are consistent with self-efficacy mediating the relations between social support and dietary intake of saturated fat, fast food, fruit and vegetable in low-income postpartum women who were overweight or obese. Conclusion: Dietary interventions aiming to decrease saturated fat and fast food intake and increase fruit and vegetable intake for the target population may consider including practical skills for increasing social support and self-efficacy that can be implemented in daily life.